Revised clinical and molecular risk strata define the incidence and pattern of failure in medulloblastoma following risk-adapted radiotherapy and dose-intensive chemotherapy: results from a phase III multi-institutional study. Issue 7 (11th December 2021) - Lucas, John T; Tinkle, Christopher L; Huang, Jie; Onar-Thomas, Arzu; Srinivasan, Sudharsan; Tumlin, Parker; Becksfort, Jared B; Klimo, Paul; Boop, Frederick A; Robinson, Giles W; Orr, Brent A; Harreld, Julie H; et al.
Abstract: Background: We characterize the patterns of progression across medulloblastoma (MB) clinical risk and molecular subgroups from SJMB03, a Phase III clinical trial. Methods: One hundred and fifty-five pediatric patients with newly diagnosed MB were treated on a prospective, multi-center phase III trial of adjuvant radiotherapy (RT) and dose-intense chemotherapy with autologous stem cell transplant. Craniospinal radiotherapy to 23.4 Gy (average risk, AR) or 36-39.6 Gy (high risk, HR) was followed by conformal RT with a 1 cm clinical target volume to a cumulative dose of 55.8 Gy. Subgroup was determined using 450K DNA methylation. Progression was classified anatomically (primary site failure (PSF) +/– distant failure (DF), or isolated DF), and dosimetrically. Results: Thirty-two patients have progressed (median follow-up 11.0 years (range, 0.3–16.5 y) for patients without progression). Anatomic failure pattern differed by clinical risk ( P = .0054) and methylation subgroup ( P = .0034). The 5-year cumulative incidence (CI) of PSF was 5.1% and 5.6% in AR and HR patients, respectively ( P = .92), and did not differ across subgroups ( P = .15). 5-year CI of DF was 7.1% vs. 28.1% for AR vs. HR ( P = .0003); and 0% for WNT, 15.3% for SHH, 32.9% for G3, and 9.7% for G4 ( P = .0024). Of 9 patients with PSF, 8 were within the primary site RT field and 4 represented SHH tumors. Conclusions: The low incidence of PSF following conformal primary site RT is comparable to prior studies using larger primary site or posterior fossa boost volumes. Distinct anatomic failure patterns across MB subgroups suggest subgroup-specific treatment strategies should be considered.